FIGURATIVE LANGUAGE IN MALAY SONG LYRICS - Muthia Delfhi; I Wayan Dirgeyasa Tangkas (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This objectives of the study were aimed to find out the types and the literal meaning of figurative language in Malay song lyrics. By using descriptive qualitative method, the writer  analyzed the selected Malay songs from different album, the data were Makan Sirih, Kuala Deli, Hitam Manis, Tanjung Katung and Sri Taman. Therefore each of figurative language filtered by using the collective method that from the five songs which were analyzed one by one to gain the results directly. The writer found 44 data that emerged in those selected Malay songs. 11 out of 13 types available from the theory, which were Simile with 1 (2,5%), Metaphor with 2 (5%), Personification 13 (29,5%), Hyperbole 3 (6%), Metonymy 1 (2,5%), Synecdoche 4 (9%), Symbol 1 (2,5%), Apostrophe 1 (2,5%), Irony 12 (27%), Paradox 5 (11%), and Pleonasm 1 (2,5%). From the data, Personification was the most dominant types of figurative language used in the 5 Malay song lyrics, by knowing the circumtances of the Personification itself was the imagery that representing love, woman, life, etc.